Issues Concerning Investor-State Dispute Settlement and the Idea of World Investment Court - Jamila, Fadilla; Amin Daud, Aidir; Sakharina, Iin Karita; Rompegading, A. Melantik; Yunus, Ahsan (International Journal of Psychosocial Rehabilitation, 2020)
Investor-State Dispute Settlement is a settlement dispute system in the field of investment law. However, as it turns out into practice along the way it tends to adjudicate disputes which implicate public law matters and affects public interest in the host state. It is now becoming a controversial topic. This study is a normative-legal research by using statute, case, and conceptual approaches. The results show that ISDS as an investment dispute settlement mechanism has received number of critics along its operations. Firstly, it lacks of transparency. Secondly, it has produced inconsistent decisions. Thirdly, its arbitrators lacks of independency and accountability. Last but not least, it often impugned the host state’s right to regulate on behalf of public interest. In order to work effectively, WIC should reform the drawbacks of the previous system. It is urged to have transparency and become more open to public as investment disputes have big impact on public interest.